2017
DOI: 10.20944/preprints201710.0076.v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Addressing Complexities of Machine Learning in Big Data: Principles, Trends and Challenges from Systematical Perspectives

Abstract: The concept of 'big data' has been widely discussed, and its value has been illuminated throughout a variety of domains. To quickly mine potential values and alleviate the ever-increasing volume of information, machine learning is playing an increasingly important role and faces more challenges than ever. Because few studies exist regarding how to modify machine learning techniques to accommodate big data environments, we provide a comprehensive overview of the history of the evolution of big data, the foundat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Machine learning can be effective in biosignal processing for several reasons. First, machine learning can handle complex and noisy data that are often encountered in biosignal processing [10]. Second, machine learning can discover hidden patterns and features that are not obvious or known beforehand [11].…”
Section: Introductionmentioning
confidence: 99%
“…Machine learning can be effective in biosignal processing for several reasons. First, machine learning can handle complex and noisy data that are often encountered in biosignal processing [10]. Second, machine learning can discover hidden patterns and features that are not obvious or known beforehand [11].…”
Section: Introductionmentioning
confidence: 99%
“…However, when large-scale datasets are used for complicated tasks, complete and perfect annotations are no longer viable, due to the reality that labeling process for these datasets is labor-intensive, costly in terms of time and money, and dependent on domain experience. With the increase of dataset volume, the learning system tends to generalize better, but the cost of annotation dramatically increases [2]. Meanwhile, former studies have revealed that obtaining the ground truth label of a dataset not only requires the participation of a large number of experts in the field, but also takes more than 10 times longer to label the instance as to collect it [3].…”
Section: Introductionmentioning
confidence: 99%